2019
DOI: 10.1097/sap.0000000000001911
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Fisher, Mohler, and Millard Techniques of Cleft Lip Repair Surgery With Eye-Tracking Technology

Abstract: Background Cleft lip repair is essential to restoring physiologic function and ensuring social and psychological well-being in children with orofacial clefts. It is important to critically study various techniques to understand the elements of the lip and nasal repair that contribute to favorable results. Here, we use eye-tracking technology to evaluate how viewers analyze images of cleft lips repaired by the Fisher, Millard, or Mohler techniques. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…6,7,10 Our study found a statistically significant improvement in scar scores when the Fisher's technique of cleft lip repair was used. The results are in keeping with other evidence previously described by Kwong and colleagues 18 and Mittermiller and colleagues. 19 Further limitations include the retrospective nature of this study and reliance on parents' recall.…”
Section: Problematic Scarring Following Facial Surgery Is a Challenging Complication Often Causingsupporting
confidence: 93%
“…6,7,10 Our study found a statistically significant improvement in scar scores when the Fisher's technique of cleft lip repair was used. The results are in keeping with other evidence previously described by Kwong and colleagues 18 and Mittermiller and colleagues. 19 Further limitations include the retrospective nature of this study and reliance on parents' recall.…”
Section: Problematic Scarring Following Facial Surgery Is a Challenging Complication Often Causingsupporting
confidence: 93%
“…Another study published recently by Kwong et al 12 used eye-tracking technology to compare rotation-advancement repairs to the anatomic subunit repair. The study presented data suggesting that viewers from multiple levels of training found cleft lips repaired with the Fisher technique to be more aesthetically pleasing than those repaired with Mohler or Millard techniques.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome further supports our data, which suggests that superior aesthetic outcomes can be achieved with the Fisher technique for cleft lip repair. The study by Kwong et al 12 offers a more objective evaluation of cleft lip repair outcomes, but it does not have a complete sample of all consecutive cleft lip repairs performed by the senior author. This study uses surgeon revision rates as a proxy for the quality of surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Kwong et al in 2019 performed a comparative study between Fisher, Millard, and Mohler techniques of cleft lip repair surgery and assessed the results using eye-tracking technology; and concluded that Fisher repairs were the best esthetically, then Mohler repairs and finally Millard repairs [23].…”
Section: Discussionmentioning
confidence: 99%